Fungsi Manajemen Diri Siswa SLTP dalam Memahami Pembelajaran Pendidikan Agama Islam (PAI) - Mindani, Mindani (AT-TALIM, 2014)
In this paper the writer discusses the function of studentsâ self management in understanding Islamic learning and tries to relate it with general management function as a controlling system in learning.Â  The indicators of studentsâ self management function will be seen in the following learning process such as the ability to set the goal of learning, monitor and evaluate the learning activity, and provide self reinforcement. Furthermore, it will also discuss about the implementation of studentâs self management through some indicator; students, school and institution in applying learning management. Afterwards, it will also elaborate about to value, management and Islamic value and applying the studentâs self management in learning process.CopyrightÂ Â©Â 2014Â by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v21i1.73